A new heterogeneous host–guest catalytic system as an eco-friendly approach for the synthesis of cyclic carbonates from CO2 and epoxides. (20th September 2018) - Mirabaud, Anaïs; Martinez, Alexandre; Bayard, François; Dutasta, Jean-Pierre; Dufaud, Véronique
Abstract : New host–guest catalytic systems were immobilized on silica supports and evaluated in the synthesis of cyclic carbonates from CO2 and epoxides. Abstract : Two strategies have been explored towards the heterogenization of a host–guest catalytic system where either cavitand host[3 i PO] or quaternary ammonium catalysts are grafted on silica supports. The bis-propargyl substituted triphosphonate cavitand[3 i PO] was clicked onto an azido functionalized ultra-large pore SBA-15 type silica (UL-SBA-15 ). Ammonium hybrid materials were produced by grafting a propyltrimethylammonium chloride silane precursor onto silicas of varying porosities and textural properties (UL-SBA-15, SBA-15 and SiO2 ). Extensive characterization of each material is presented (XRD, N2 sorption, TGA, solid state NMR, elemental analyses, FT-IR). The effect of heterogenization was investigated in the coupling of CO2 with styrene oxide and was compared to all-soluble cavitand/ammonium homogeneous analogs.